2013
DOI: 10.1172/jci60806
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 is essential for DNA replication in hematopoietic progenitor cells

Abstract: Histone deacetylase 3 (HDAC3) contributes to the regulation of gene expression, chromatin structure, and genomic stability. Because HDAC3 associates with oncoproteins that drive leukemia and lymphoma, we engineered a conditional deletion allele in mice to explore the physiological roles of Hdac3 in hematopoiesis. We used the Vav-Cre transgenic allele to trigger recombination, which yielded a dramatic loss of lymphoid cells, hypocellular bone marrow, and mild anemia. Phenotypic and functional analysis suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 59 publications
8
98
0
Order By: Relevance
“…While deletion of Hdac3 in Tregs led to increased expression of genes that were unaffected when HDAC3 was deleted in other cell types ( Figure 9F), for the most part there were similar changes in gene expression ( Figure 9G), as was reported for Hdac3 deletion in nonlymphoid cells (33)(34)(35)(36)(37)(38)(39)41). Overall, Hdac3 deletion led to altered expression of a wide variety of genes in Tregs, including those promoting activation of NF-κB and other proinflammatory pathways.…”
Section: Osteo-chondroprogenitor Cells (37) Hippocampal Cells (38) supporting
confidence: 67%
“…While deletion of Hdac3 in Tregs led to increased expression of genes that were unaffected when HDAC3 was deleted in other cell types ( Figure 9F), for the most part there were similar changes in gene expression ( Figure 9G), as was reported for Hdac3 deletion in nonlymphoid cells (33)(34)(35)(36)(37)(38)(39)41). Overall, Hdac3 deletion led to altered expression of a wide variety of genes in Tregs, including those promoting activation of NF-κB and other proinflammatory pathways.…”
Section: Osteo-chondroprogenitor Cells (37) Hippocampal Cells (38) supporting
confidence: 67%
“…While such general changes in chromatin architecture may play a role in the generation of replication stress after HDAC inhibition, disruption of HDAC functions may also directly affect replication, as very short treatment with histone deacetylase inhibitors (HDIs) still generated robust reductions in the rates of replication fork progression (112,128). In cutaneous T-cell lymphoma (CTCL) cell lines treated with both broad-spectrum and HDAC3-selective inhibitors, the effects of HDI treatment on replication fork velocity were observed before the accumulation of global increases in histone acetylation (128).…”
Section: Figmentioning
confidence: 99%
“…Finally, it is likely that HDAC functions in replication control and maintenance of genome stability contributes to the phenotypes observed in mouse deletion models. For instance, replication stress was recently observed in a model of Hdac3 deletion in hematopoietic stem cells (112).…”
Section: Hdis Alter Gene Expression But Is It Important?mentioning
confidence: 99%
“…have ventricular dysfunction that elevates intracardiac pressure on the thinner-walled atrium, which induces chronic inflammation and, in turn, structural remodeling and a predisposition to sustained AF. HDACs, in particular class I HDACs, promote the maturation of adipocytes and inflammatory cells that produce inflammatory cytokines (Haberland et al, 2010;Summers et al, 2013). In our dog model, we could assess not only atrial and circulating levels of TNFa and interleukins but also their cardiac production, which increased during AF and was mostly normalized by CI-994.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, only mature immune cells and adipocytes release inflammatory cytokines, and class I histone deacetylases (HDACs) promote the differentiation and maturation of these cell types (Haberland et al, 2010;Yamaguchi et al, 2010;Summers et al, 2013). We previously showed that the pan-histone deacetylase inhibitor trichostatin A reverses established atrial fibrosis and inducible atrial arrhythmias, without affecting cardiac chamber size, function, or hemodynamics in transgenic mice overexpressing the transcription factor homeodomain-only protein (Hopx Tg ), a model of ventricular hypertrophy (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%